Liver abscess drainage by needle aspiration versus pigtail catheter: a prospective study - Khan, Arshad; Tekam, Vijay Kumar (International Surgery Journal, 2017)
Background: Liver abscess is a disease of frequent occurrence which figures prominently in the differential diagnosis of upper abdominal and right lower respiratory tract diseases. These includes a recent increase in incidence reflecting more accurate diagnostic techniques especially after 1965 with the advent of radioisotopes scan and later on ultrasonography and CT scan. The reduction in mortality from 90% at the turn of century to the estimated 10-20% today cannot be ascribed to surgery alone. Methods: The study was conducted on 65 patients of liver abscess. Two compared modalities of percutaneous treatment of liver abscess were (1) needle aspiration and (2) pigtail catheter aspiration. All interventions were performed under ultrasonographic guidance. Only those patients having liver abscess/abscesses greater than 5 cm in at least one dimension, liquified & drainable were included in this study. Results: Amoebic liver abscess (63.33%) were more common than pyogenic liver abscess (26.67%). Clinical recovery was significantly earlier in catheter group (average 5 days) than in needle aspiration group (average 6.29 days) (p value 0.001). Average duration of i.v. antibiotic is significantly shorter in catheter group (6.4 days) than in needle aspiration group (9.5 days) (p value 0.002). Conclusions: Thus, our study concluded that in view of greater volume of pus drained in first sitting, early clinical recovery, shorter duration of hospital stay and slightly more success rate continuous catheter drainage is effective percutaneous treatment modality than intermittent needle aspiration.